Facilitating the adoption of experience capitalization to inspire change - Gbakie, Emmanuel Sahr (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Rural Finance and Community Improvement Programme Phase II (RFCIP II) in Sierra Leone has started several experience capitalization activities, from organising and facilitating training workshops for key project staff, to producing knowledge products and sharing them with other development programmes. This article highlights some of the key steps taken for the adoption of the approach, as well as the lessons learnt and the way forward.